Can Islamic Law and Secular Law Coexist Without Conflict - Haider, Aftab; Mathlouthi, Naim; Saer Rahal, Mohamed; Afzal, Jamil (Institut Agama Islam Negeri Curup, 2025)
The coexistence of Islamic law and state legal systems presents significant challenges, especially in multicultural societies, where multiple legal systems intersect and influence governance, human rights, and societal integration. Despite significant interest in the concept of legal pluralism, there is still a lack of clarity on how these two legal frameworks can work together without causing conflicts, especially when it comes to issues like family law, human rights, and governance. Through a detailed comparison of case studies, legal texts, and real-life examples, the research identifies areas where these legal systems overlap and clash, particularly regarding gender equality, the protection of human rights, and jurisdictional conflicts. The study also looks at potential solutions, such as legal reforms and the creation of hybrid legal bodies that can help complement the two systems. The findings suggest that while there are significant challenges in balancing these systems, there are also opportunities for greater cooperation and understanding. This article emphasizes the importance of legal reforms, improved communication between legal authorities, and the creation of shared spaces where both legal systems can coexist more effectively. It aims to provide practical insights for legislators and legal practitioners to improve the way these legal frameworks work together, eventually promoting justice and social cohesion in multicultural societies